Influence of the color scale in qualitative assessment of brain perfusion imaging - Santos, Wilson (2022)
Introduction – Brain perfusion imaging (BPI) is an imaging study that allows the acquisition of three-dimensional tomographic images of the biodistribution of a tracer, reflecting regional brain perfusion. Therefore, the color scale used has a major role in the clinical interpretation of these images. Aim – To study the influence of the color scales in qualitative evaluation of the BPI and to conclude which are the most appropriate scales for the visual analysis. Methods – Thirty-one BPI studies were visually analyzed by 15 operators divided into two classes: operators without professional experience (10) and operators with professional experience (5) using the Cool, Gray, Gray Invert, Thermal, and Perfusion color scales. For the Cool color scale, the image analysis was performed through a semiquantitative score system. The remaining color scales were evaluated by comparison with the analysis of the images performed with the Cool color scale. Non-parametric Friedman Test was used to assess the interoperator variability (relative to the Cool color scale). The results obtained with the remaining color scales were evaluated according to the percentage of symbols the participants assigned during their visual analysis of the 31 studies. Results – Inter-operator variability has shown statistically significant differences among all participants (p<0.05). The results for the Perfusion color scale were the closest to the brain perfusion with Cool, and so is an alternative color scale for evaluation of brain perfusion images. Regarding Gray, Gray Invert, and Thermal color scales, their results were divergent, and thus should not be considered optimal for brain perfusion interpretation. Conclusion – The color scale selected can influence the qualitative assessment of BPI. Perfusion can be implemented in clinical practice as an alternative color scale for the analysis of BPI studies. Gray, Gray Invert, and Thermal color scales should not be considered optimal for brain perfusion interpretation.